Estimates of the Non-accelerating Inflation Rate of Unemployment (NAIRU) for Hungary - Lajos Tamás Szabó (Magyar Nemzeti Bank, 2015)
Labour market tightness, that is the ratio of jobs to the unemployed, has an impact on wage setting, which also affects inflation. Among other things, the unemployment gap, which is the difference between unemployment rate and non-accelerating inflation rate of unemployment (NAIRU), is used to measure inflationary pressure from the labour market. This paper examines which of the NAIRU estimation methods described in the literature can be applied to Hungary. In evaluating the results, the revisional property of the NAIRU is also examined, as well as the forecast capacity of the unemployment gap with regard to wages. Based on these, the model containing the tightness indicator performs the best. This is notable from a forecasting perspective, because the vast majority of estimates in the literature use wages to provide an estimate of the unemployment gap. Therefore, an indicator which does not use wages at all to estimate the unemployment gap performs the best in forecasting wage growth. Based on the estimation the NAIRU has decreased in recent years. Of the factors affecting the NAIRU, the variables describing the general macro environment (total factor productivity, long-term unemployed, number of persons employed in construction, risk premium) have considerablely contributed to the decrease in the NAIRU, which may have been complemented by changes in labour market institutions. Based on the literature, the latter may be useful when explaining the differences between countries. For the estimation of these factors' effects (e.g. decrease in the tax wedge, transformation of the unemployment benefit system etc.) further research is necessary. Within the framework of the sensitivity analysis, if the groups which are loosely linked to the labour market (e.g. discouraged workers) are also regarded as part of the free labour force capacity, the view of the tightness of the labour market (the unemployment gap) does not change. However, the results are sensitive to the assumption made about the labour market status of fostered workers.
Keywords: E24; J21; J69; 330; NAIRU; unemployment; wages; vacancies